Treating the invisible: Subclinical actinic keratosis detected by imiquimod - Daisy Kopera; Joachim Torrano; H. Peter Soyer (Wiley, 2023)
Abstract Background Skin in UV‐exposed areas may develop UV‐induced actinic damage in DNA sequences leading to proliferation of keratinocyte carcinoma, a type of non‐melanoma skin cancer. Actinic keratosis (AK) represents early‐stage in situ squamous cell carcinoma. It develops from the basal cell layer and may be present in subclinical stages, being reported as field cancerization, even before being clinically visible. Thus, we hypothesise that from the age of 50 + UV‐exposed skin features subclinical forms of AKs without visible skin lesions. Objectives This study aims at clarifying the existence of the clinically invisible, early stages of AKs on chronically UV‐exposed skin without showing clinically evident features of AK. Methods 46 volunteers (26 females and 20 males) aged 50+ with signs of moderate to severe UV‐damage (photodamage) applied imiquimod 3.75% creme on their entire face every night for a 2‐week period. All participants kept a diary noting onset, severity of inflammatory reactions, and unexpected side effects. Results More than 90% of participants without clinical evidence of AK showed inflammatory reactions on topical treatment with imiquimod on their face demonstrating an interaction between UV‐damaged mutated keratinocytes and the topically applied immunomodifier, thus proofing the presence of subclinical AKs. Conclusions The action of imiquimod is not restricted to visible AK lesions, but often includes their vicinity, suggesting that neoplastic processes are frequent at a cellular level, not confined to clinically evident lesions, supporting the concept of field cancerization. Thus, subclinical AKs do exist in an early, macroscopically invisible state and may be targeted by imiquimod or 5‐FU. At this stage, AKs are being treated before diagnosis by usual clinical means, and well before potential progression to invasive squamous cell carcinoma (SCC). Eventually, imiquimod 3.75% cream could be recommended in UV‐exposed skin to prevent the presumptive development of AK and later on, early SCC.